PENGARUH HARGA, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN - HERI DIYAN KURNIAWAN (JURNAL EKOBIS DEWANTARA, 2018)
The purpose this experiment is to describe (1) the effect of price on consumer purchase decisions on JNE services Jl. Glagahsari No. 62 Yogyakarta, (2) the effect of service quality to consumer purchase decisions on JNE services Jl. Glagahsari No. 62 Yogyakarta, (3) influence on purchase decisions on the location of the consumer JNE services Jl. Glagahsari No. 62 Yogyakarta. The population in this study is that consumers on JNE services Jl. Glagahsari No. 62 Yogyakarta. The number of consumers that are used in this study sebanayak 120 people. Methods of data collection was done by using kuesioer media, while the technique of data analysis using multiple linear regression analysis were supported by the coefficient of determination and t test. And also test the classical assumption of normality test, test and test heteroskedastisitas multicoloniarity. The results showed that (1) the price positive and significant impact on consumer purchasing decisions JNE services Jl. Glagahsari No. 62 Yogyakarta., (2) quality of service is not positive and significant impact on consumer purchasing decisions JNE services Jl. Glagahsari No. 62 Yogyakarta., (3) the location is not positive and significant impact on consumer purchasing decisions JNE services Jl. Glagahsari No. 62 Yogyakarta.